ألفاظ الحزن والأمل في "أغاني الحياة" لأبي القاسم الشّابّي نماذج من قصائد مختارة -دراسة دلاليّة - مريم عمارة (My University, 2024)
summary: The research aims to study the phenomena of “sadness and hope” in five selected poems: “The Will to Live,” “O Night,” “Song of Sorrows”،“Ode to the Mighty,” and “The Orphan’s Complaint.” And analyze it from a semantic perspective. Semantic studies have received wide attention among scholars and researchers, whether in the Arab or Western world, where their opinions focused on the importance of semantics and its theories. The theory of semantic fields is considered among the most prominent of these theories, as it has imposed itself as an important tool in analyzing vocabulary in various fields and concepts related to meaning. This theory is considered one of the pivotal points in the development of modern semantics. Abu Al-Qasim Al-Shabbi is considered an ideal example of a poet who used his pen and poetry to embody the issues of his people. Where he wove the pain and suffering he went through into purposeful poetic verses, involving the poet’s psychological state and vast imagination. In his poetry, he mixes sadness and hope, inspiring the reader to be optimistic about life despite the difficult challenges. -------------------------------- ملخص يهدف البحث إلی دراسة ظاهرتي "الحزن والأمل" في خمسٍ قصائد مختارة وهي: "إرادة الحياة"، "أيّها اللّيل" "أغنية الأحزان"، "نشيد الجبّار"، و"شكوى اليتيم".وتحليلها من منظور دلاليّ. الدّراسات الدّلاليّة نالت اهتمامًا واسعًا بين الدّارسين والباحثين، سواء في العالم العربيّ أو الغربيّ، حيث ركّزت آراؤهم على أهمّية علم الدّلالة ونظرياته. وتعتبر نظريّة حقول الدّلالة من بين أبرز هذه النّظريّات، حيث فرضت نفسها كأداة مهمّة في تحليل المفردات في مختلف المجالات والمفاهيم المتّصلة بالمعنى، وتعدّ هذه النّظريّة من النّقاط المحوريّة في تطوّر علم الدّلالة الحديث. يعتبر أبو القاسم الشّابّي نموذجاً مثاليّاً للشّاعر الذي استخدم قلمه وشعره لتجسيد قضايا شعبه، حيث نسج الألم والمعاناة الّتي مرّ بها في أبيات شعريّة هادفة، تنطوي على الحالة النّفسيّة والخيال الواسع للشّاعر. يمتزج في شعره بين الحزن والأمل، ملهماً القارئ للتّفاؤل بالحياة رغم التّحديّات الصّعبة. ----------------------- Résumé La recherche vise à étudier les phénomènes de « tristesse et d'espoir » dans cinq poèmes sélectionnés : « La volonté de vivre », « Ô nuit », « Chant des douleurs », « Ode aux puissants » et « La plainte de l'orphelin ». et de les analyser d’un point de vue sémantique. Les études sémantiques ont reçu une grande attention parmi les universitaires et les chercheurs, que ce soit dans le monde arabe ou occidental, où leurs opinions se sont concentrées sur l'importance de la sémantique et de ses théories. La théorie des champs sémantiques est considérée comme l'une des plus importantes de ces théories, car elle s'est imposée comme un outil important dans l'analyse du vocabulaire dans divers domaines et concepts liés au sens, et cette théorie est considérée comme l'un des points pivots dans le développement de sémantique moderne
Keywords: Meaning; fields of meaning; sadness; optimism; Abu Al-Qasim Al-Shabbi; ...; الدّلالة، حقول الدّلالة، الحزن، التّفاؤل، أبو القاسم الشّابّي; Sens; champs de sens; tristesse; optimisme